Hubungan Self Efficacy dan Motivasi Belajar dengan Kemampuan Pemecahan Masalah Matematis Siswa SMA pada Materi SPLTV - Gustia, Satria Kamal; Esti Ambar Nugraheni (FKIP Universitas Mataram, 2025)
This research aims to determine whether there is a significant relationship between self-efficacy and mathematical problem solving abilities, as well as between learning motivation and mathematical problem solving abilities. Apart from that, this research also aims to find out whether there is a significant relationship between self-efficacy and learning motivation together with the mathematical problem solving abilities of class X students at SMAN 1 Tajurhalang on SPLTV material. This research uses a quantitative approach with correlational methods. The population in this study included all 360 class X students, with a sample of 199 students from six classes. Data collection was carried out through tests to measure mathematical problem solving abilities on SPLTV material, as well as questionnaires that measured students' levels of self-efficacy and learning motivation. The results of the analysis using the Pearson correlation coefficient and multiple correlation show that there is a significant relationship between self-efficacy and mathematical problem solving ability, with a value of r = 0.202 which is classified as a low relationship. Meanwhile, the relationship between learning motivation and mathematical problem solving ability obtained a value of r = 0.194, which is in the very low category. Further analysis also shows that together, self-efficacy and learning motivation have a significant relationship with mathematical problem solving abilities, with a value of r = 0.211 which is in the low relationship strength category.